Kewenangan Badan Arbitrase Nasional dalam Penyelesaian Sengketa Bisnis di Indonesia - Khaerurrizal Khaerurrizal; Taufik Firmanto; Adnan Adnan (Jurnal Hukum Lex Generalis, 2025)
This study examines the authority of the Indonesian National Arbitration Board (BANI) in resolving business disputes in Indonesia. Using a normative legal research method, this study explores the legal basis of arbitration and the implementation of BANI's authority based on applicable laws and regulations. The results of the study indicate that BANI has legitimate authority, but there are still obstacles in the implementation of arbitration decisions. In conclusion, strengthening BANI's role and legal certainty are needed to increase the effectiveness of resolving business disputes through arbitration.